Monetary Policy in Fossil Fuel Exporters The Curse of Horizons - Arezki, Rabah (World Bank E-Library Archive, 2019)
This paper examines the role of monetary policy in fossil fuel exporters at different horizons. The main argument is that central banks in these economies need to look beyond the horizon of the business cycle. In the short run, (independent) monetary policy should flexibly target inflation. In the medium run, central banks need to coordinate with fiscal authorities to ensure that monetary policy operates around a credible and sustainable fiscal anchor. In the long run, central banks should beware of the existential threats posed by new risks related to stranded assets